Peran Kelembagaan Agribisnis Usaha Tanaman Hias di Kota Kendari - Selvi Selvi; La Ode Alwi; La Ode Kasno Arif (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Ornamental plants in Kendari City need an agribusiness institution that regulates ornamental plant business management to improve quality and traders' access to technology, markets and capital. Furthermore, technology is gradually increasing, increasing resources, helping ease access to facilities provided by the government (credit, facilities and infrastructure), and supporting every agribusiness subsystem and government policies. This research was conducted at the Promotion and Sales Location of Agricultural Products in Kendari City, on Jalan Ahmad Yani, Bende Village, Kadia District, Kendari City, from June to November 2021. This study aimed to determine the types and roles of ornamental plant agribusiness institutions in Kendari City. This study has 15 populations, where sampling uses the census method, which means that researchers take the location of promotion and sale of agricultural products in Kendari City. The variables observed in this study are the roles and working mechanisms of agribusiness institutions using qualitative descriptive analysis. The results showed that the role of ornamental plant agribusiness institutions in Kendari City was divided into four agribusiness subsystems: production facilities institutions, farming/cultivation institutions, marketing institutions and supporting service institutions.